Improvement of parameters and conditions for magnetron sputtering of WO3 layers to enhance their electrochromic performances. (2020) - Semenova, Anna; Eruzin, Alexander; Bezrukov, Pavel; Sychov, Maxim; Mjakin, Sergey; Lukashova, Tatiana; Sudar, Nikolay
Abstract: Optical performances (light transmission in the colored and bleached states) of electrochromic devices (ECDs) comprising SnO2 -WO3 -electrolyte (1 M LiClO4 solution in propylene carbonate)-SnO2 layers are studied depending on tungsten oxide (WO3 ) electrochromic layer deposition time via reactive magnetron sputtering in oxygen-argon mixture at pressure 0.15 Pa. The optimal WO3 layer sputtering time is 750 s in the case of support movement during the deposition while for motionless supports this value is 200 s. The effect of the deposited WO3 layers heat treatment at 450 °C upon their electrochromic performances is studied.